2010
DOI: 10.1111/j.1751-1097.2010.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

UV Exposition During Typical Lifestyle Behavior in an Urban Environment

Abstract: In this study the personal exposure to solar UV radiation in an urban environment was measured. Lifestyle in an urban environment is characterized by staying indoors during most of the day. Furthermore, the ambient UV radiation is mitigated by shadowing by buildings. The aim of the study was to find out activities which may contribute to UV-induced health risk in a low exposure environment. Exposure was measured during typical outdoor activities: shopping, walking, sitting in a sidewalk café, cycling, sightsee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Compared to measurements made to sunbathers, who also spend a significant period of time in a horizontal orientation, the measurements of ER made here show that snorkelers experience similar ratios of ambient exposure as those experienced by beachgoers (7) and poolside sunbathers (8), with this ratio increasing during periods when the sun is positioned at oblique SZA ranges. Siani et al (7) measured the ER to the chests of beachgoers using PS dosimeters.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…Compared to measurements made to sunbathers, who also spend a significant period of time in a horizontal orientation, the measurements of ER made here show that snorkelers experience similar ratios of ambient exposure as those experienced by beachgoers (7) and poolside sunbathers (8), with this ratio increasing during periods when the sun is positioned at oblique SZA ranges. Siani et al (7) measured the ER to the chests of beachgoers using PS dosimeters.…”
Section: Discussionsupporting
confidence: 39%
“…This study (6) determined that Hawaiian beachgoers spend an average of 3 hours at the beach and experience an exposure of approximately 1040 Jm -2 of erythemally effective UVR in that time. Exposure distributions to seaside sunbathers (7) and those received in proximity to a pool (8) have also been studied. However, specific measurements of UVR exposure to snorkelers are not present in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from existing studies for Austrian conditions (e.g., Schauberger et al [17], Schmalwieser et al [18,19]), a variety of exposure measurements on different subgroups can be found in the literature. Due to different methodological approaches, findings reported in these studies are not directly comparable.…”
Section: Introductionmentioning
confidence: 99%
“…Certain features and materials like glass windows, trees or walls exert different effects on the incoming radiation (i.e. reflection, filtering and absorption) [4,[23][24][25][26]. Although it is not within the scope of this article to analyse these particular effects, the proposed methods will allow researchers to map SVFs for large cities at a very high resolution, while maintaining detailed descriptions of urban canopy shapes and colours, which in turn could be related to the underlying materials.…”
Section: Introductionmentioning
confidence: 97%
“…Because of the unique microclimate conditions created by the specific geometry of each canyon, urban geometries affect the energy performance of buildings and, since main outdoor activities occur at these spaces, they also play a crucial role in human thermal comfort in streets [2,3]. Human exposure to sunlight within urban canyons is also a relevant health issue due to the diverse biological effects of ultraviolet light [4,5]. Some of the future aims of our study will include spectral irradiance calculations within urban canyons in order to determine urban solar UV patterns, as an aid for health studies.…”
Section: Introductionmentioning
confidence: 99%